Pengembangan Modul Materi Barisan dan Deret Kelas X SMK dengan Pendekatan REACT - Kristina Kewa Sili; Siti Napfiah; Anik Kurniawati (Program Studi Pendidikan Matematika, 2018)
Module constitutes one of material teach applicable to increase learning quality. Largely student most constraint studies mathematics because terminological they that mathematics abstraction. Berdasakan it is developed module which concern material with student real life. One of approaching in mathematics that gets bearing with student real life is REACT'S approaching (Relating, Experiencing, Applying, Cooperating, Transferring). To the effect this research is develop module that valid and paktis on Line and Line material with REACT'S approaching. This observational type constitute development research with model developmental ADDIE who covers five subject steps, which is analysis, design, development, implementation, and evaluation. Instrument that is utilized is sheet validate material pro, sheet validates media pro, and student response questionnaire. Subjek is this research is SMK'S student Ile Boleng's Country brazes X. Kevalidan module reaches score percentage average 77%. Seen from practicability aspect, practical stated module with score percentage average 95% by pretty good categories.